Respuestas
Respuesta dada por:
4
Respuesta:
6x4 + x3 - x +(6x4 + 2x2): (2x2) – 2x:(4x3 - 1) = 31 + 20x/11
Explicación paso a paso:
6x4 + x3 - x +(6x4 + 2x2): (2x2) – 2x:(4x3 - 1) =
= 24 + x2 + (24 + 4) : 4 - 2x : (12-1) =
= 24 + x2 + 28 : 4 - 2x : 11 =
= 24 + x2 + 7 - 2x/11 =
= 31 + 2x - 2x/11 =
= 31 + 22x/11 - 2x/11 =
= 31 + 20x/11
JZG08:
dame coronita plsss :·
Respuesta dada por:
2
Respuesta:
136-20x
Explicación paso a paso:
24+3X-X+(24+4)x4-2Xx(12-1)
24+3X-X+28x4-2Xx11
24+3X-X+112-22X
136-20X
NOTA:
X=equis
x=multiplicación
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años